ETHNO-GEOGRAPHIC FEATURES OF THE SETTLEMENT FORMATION OF DAGESTAN MOUNTAINEERS (XIX - early XX century) - Ramazanova, Z B (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the problem of ethnogeographical features of settlement development of Dagestan mountaineers in the 19th–early 20th cc. Special attention is given to the culture of nature management and displacement of the population (economy and settlement system, which determine the man’s attitude to natural resources and space). Basing on the field and literature data concerned with the problem, the author points out that a number of factors (physical-geographical, environmental, economic, etc.) had an impact on the process of settlement development (the system of displacement) of the population of Mountainous Dagestan during the period under review.